An accessory head of abductor pollicis longus: clinical and anatomical implications - Bindusar K,; Ranjeeta H,; Susmita S,; Vandana Mehta,; Rajesh KS, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
An accessory belly of abductor pollicis longus (APL), discovered in the right limb of a cadaver emanating from the main muscle belly was seen to insert onto the tendon of brachioradialis, 3.5 cm proximal to the extensor retinaculum. Measuring 2cm in length, this accessory fleshy belly was seen to bridge over the flexor carpi radialis longus and insert onto the brachioradialis tendon extending for 2 cm along its length. The tendon of APL was inserted by dividing into a superficial and a deep tendon. Such anomalies may be important during surgeries of the hand and especially during reconstruction surgeries involving the APL. The insertion of the accessory belly of APL on the brachioradialis may connote sharing of tendon by two muscles and may have impact on the dynamics of thumb movement when there is simultaneous contraction of both the muscles.